Microalgae biopeptides applied in nanofibers for the development of active packaging - Gonçalves,Carolina Ferrer (2017)
Abstract This study was conducted to develop PCL nanofibers with the incorporation of microalgae biopeptides and to evaluate the stability of chicken meat cuts during storage. PCL and PCL/biopeptides nanofibers were formed by electrospinning method, and the diameters obtained were 404 and 438 nm, respectively. The tensile strength, elongation, melting temperature and thermal stability of biopeptide-added PCL nanofibers were 0.245 MPa, 64%, 56.8 °C and 318 °C, respectively. PCL/biopeptide nanofibers showed a reducing power of 0.182, inhibition of 22.6% and 12.4% for DPPH and ABTS radicals, respectively. Chicken meat cuts covered by the PCL/biopeptide nanofibers showed 0.98 mgMDA∙kg-1 and 25.8 mgN∙100g-1 for TBARS and N-BVT analysis, respectively. Thus, the PCL/biopeptide nanofibers provided greater stability to the product and control of oxidative processes ensuring the product quality maintenance during the 12 d of storage.